Estimation of the Peak Performance in the 100-Meter Breast Stroke on the Basis of Serum Lactate Measurement during Two Submaximal Test Heats at Different Velocities - Elliott, M.; Haber, P. (Biomechanics and Medicine in Swimming, 1983)
Medical supervision of training is becoming more and more important. The methods used should be practical not only in the laboratory but also at the training place and they should be adjusted to the particular form of sport. Forms of competitive sports favoring short-time endurance require reliable methods for judging special endurances, which can be defined as the optimal combination of special strength and techniques as well as aerobic and anaerobic capacity required for the length of the competition. Provided the competition does not last significantly longer than 2 min, the necessary energy is provided mainly through the lactacid anaerobic system. Serum lactate is a measure of the rate of glycolytically formed energy and thus constitutes an objective measure of work intensity in short-time endurance activities. The individual's special endurance determines the relationship between serum lactate and speed. Consequently, it must be possible to estimate velocity at maximal lactate after having determined the individual relationship between lactate and velocity during submaximal work. This assumption was substantiated by comparing the actual measured maximal velocity with the estimated maximal velocity, based on this individual relationship.